How do you solve 3x^2+5x-2=0 by factoring?

1 Answer
May 24, 2018

x1=-4/6 and x2=-1

Explanation:

we need the mathematical formula B^2-4AS . B is our 5 its the one that has the x but not in any form of power so we want our x not to be an exponential. The A is our 3 which is the one that is exponential. And our S is the standard number which is -2 in this case. So by using the formula we have : 5^2-4*3*-2=1
Now we are going to use another the next part of the mathematical formula -5+sqrt1=Q =>Q/6 and our next formula for the second solution -5-sqrt1=N=>N/6
So our answers are x1=-4/6 and x2=-1
with x1 and x2 being the solutions.